2019
DOI: 10.5539/hes.v9n1p151
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Social Support in Recreational Activity Participation: A Study on Students

Abstract: The purpose of this study is to examine university students’ perceived social support level in recreational activity participation. 536 students who were selected from 3 different universities using convenience sampling participated in the study voluntarily. As data collection form; Perceived Social Support Scale (PSSS-R) and Preference Factors of Recreation Areas (PFRA) scale were used. For the analyses of the data; descriptive statistics, Independent Samples T Test used for two groups depending on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Due to such reasons as weight control, healthy life, socialization, fight against stress, disease protection, wish to forget daily problems, tendency to keep away from bad habits and to stay away from negative thoughts, entertainment, development of physical identity, using free time, development of healthy lifestyles, desire to increase self-confidence; people may tend to do physical activities. It may be suggested that one's motivational approach plays a key role in not being away from physical activities and the engagement in physical activities (Demir & Cicioğlu, 2018;Eskiler & Küçükibiş, 2019;Gumus et al, 2019;Yılmaz et al, 2019). Although fast advances in technology and the industrialization process have eased life's burdens, with the increased virtual/digital venues, people's physical activity levels have decreased and with the emergence of social media, which let them socialize, time spent on the internet has increased.…”
Section: Introductionmentioning
confidence: 99%
“…Due to such reasons as weight control, healthy life, socialization, fight against stress, disease protection, wish to forget daily problems, tendency to keep away from bad habits and to stay away from negative thoughts, entertainment, development of physical identity, using free time, development of healthy lifestyles, desire to increase self-confidence; people may tend to do physical activities. It may be suggested that one's motivational approach plays a key role in not being away from physical activities and the engagement in physical activities (Demir & Cicioğlu, 2018;Eskiler & Küçükibiş, 2019;Gumus et al, 2019;Yılmaz et al, 2019). Although fast advances in technology and the industrialization process have eased life's burdens, with the increased virtual/digital venues, people's physical activity levels have decreased and with the emergence of social media, which let them socialize, time spent on the internet has increased.…”
Section: Introductionmentioning
confidence: 99%
“…Motivational structures determine stimuli for actual participation in a specific type of leisure. For example, it is likely that those who are physically motivated may participate in leisure activities with physical components (Choi and Fu, 2015;Gumus et al, 2019).…”
Section: Introductionmentioning
confidence: 99%